Cryogenic adsorption pumps for REB accelerrators - Batrakov, A.B.; Kravchenko, V.A.; Lonin, Yu.F.; Chernyshenko, V.Ya. (Вопросы атомной науки и техники, 2004)
It is known that in relativistic electron bunching (REB) accelerators the main residual gases are air components. Under irradiation in targets made of different materials being studied, a significant increase of a level of such gases as hydrocarbons, aqueous vapor and hydrogen is observed. Therefore, it is clear that for improvement of vacuum conditions for a REB accelerator it is necessary to apply pumps which should permit to realize a high rate of pumping out of main residual gases and those of them the level of which increases considerably in targets under irradiation. We propose to complete the available equipment for pumping of REB accelerators with cryogenic adsorption pumps. They are to be placed in accelerators so that they can serve as additional means for protection of the target chamber volume against hydrocarbon coming from the available pumping equipment. It will make it possible to improve significantly the initial vacuum conditions in the working volume, and, furthermore, to reduce the time between experimental pulses.